Color-tunable polymeric long-persistent luminescence based on polyphosphazenes - Wang, Zhonghao (2020)
Organic long-persistent luminescence (OLPL) materials have attracted wide attention on account of their fascinating luminescence properties, presenting application prospects in the fields of bioimaging, information security, displays, anti-counterfeiting, and so on. Some effective strategies have been developed to promote the intersystem crossing (ISC) of the excited singlet state to triplet state and limit nonradiative transition, and thus OLPL materials with long lifetime (more than 1s) and high quantum yield have been explored. However, OLPL materials with dynamic and excitation-dependent characteristics are rarely reported. In this work, two novel polyphosphazene derivatives containing carbazolyl units are designed and synthesized successfully, and then they are doped into poly(vinyl alcohol) (PVA) films to achieve polymeric long-persistent luminescence (PLPL). Unexpectedly, excitation-dependent PLPL (ED-PLPL) is obtained under ambient conditions (in air at room temperature), and the persistent luminescence color can be changed from blue to green upon varying the excitation wavelength. At the same time, a dynamic cycle of ED-PLPL is realized based on the formation and destruction of hydrogen bonding interactions between the PVA chains and polyphosphazene phosphor. This work provides a new strategy for the design of color-tunable polymeric luminescent materials under ambient conditions.